Autophagy and senescence facilitate the development of antiestrogen resistance in ER positive breast cancer - McGrath, Michael K.; Abolhassani, Ali; Guy, Luke; Elshazly, Ahmed M.; Barrett, John T.; Mivechi, Nahid F.; Gewirtz, David A.; Schoenlein, Patricia V. (Frontiers in Endocrinology, 2024)
Estrogen receptor positive (ER + ) breast cancer is the most common breast cancer diagnosed annually in the US with endocrine-based therapy as standard-of-care for this breast cancer subtype. Endocrine therapy includes treatment with antiestrogens, such as selective estrogen receptor modulators (SERMs), selective estrogen receptor downregulators (SERDs), and aromatase inhibitors (AIs). Despite the appreciable remission achievable with these treatments, a substantial cohort of women will experience primary tumor recurrence, subsequent metastasis, and eventual death due to their disease. In these cases, the breast cancer cells have become resistant to endocrine therapy, with endocrine resistance identified as the major obstacle to the medical oncologist and patient. To combat the development of endocrine resistance, the treatment options for ER + , HER2 negative breast cancer now include CDK4/6 inhibitors used as adjuvants to antiestrogen treatment. In addition to the dysregulated activity of CDK4/6, a plethora of genetic and biochemical mechanisms have been identified that contribute to endocrine resistance. These mechanisms, which have been identified by lab-based studies utilizing appropriate cell and animal models of breast cancer, and by clinical studies in which gene expression profiles identify candidate endocrine resistance genes, are the subject of this review. In addition, we will discuss molecular targeting strategies now utilized in conjunction with endocrine therapy to combat the development of resistance or target resistant breast cancer cells. Of approaches currently being explored to improve endocrine treatment efficacy and patient outcome, two adaptive cell survival mechanisms, autophagy, and "reversible" senescence, are considered molecular targets. Autophagy and/or senescence induction have been identified in response to most antiestrogen treatments currently being used for the treatment of ER + breast cancer and are often induced in response to CDK4/6 inhibitors. Unfortunately, effective strategies to target these cell survival pathways have not yet been successfully developed. Thus, there is an urgent need for the continued interrogation of autophagy and "reversible" senescence in clinically relevant breast cancer models with the longterm goal of identifying new molecular targets for improved treatment of ER + breast cancer.